2017
DOI: 10.1039/c7ra01920c
|View full text |Cite
|
Sign up to set email alerts
|

Effect of an external electric field on the electronic properties of SnS2/PbI2 van der Waals heterostructures

Abstract: The future development of optoelectronic devices will require an advanced control technology in electronic properties, for example by an external electric field (Efield).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(7 citation statements)
references
References 45 publications
0
7
0
Order By: Relevance
“…The negative values of the binding energies suggest that all the considered vdWHs are energetically stable within the same order of magnitude as other vdW heterostructures. For instance, graphite (−116 meV), 70 blue P/BSe (−133 meV), 71 MoS 2 /SnS 2 (−100 meV), 19 BP/blue P (−120 meV), 72 SnS 2 /PbI 2 (−124 meV), 73 Cd/C 2 N (−80 meV) 74 and SiAs 2 /GeP 2 (−77.4 meV). 47 From binding energy analyses of the two different staking modes, we have concluded that the heterostructure materials prefer the AA-stacking mode over AB.…”
Section: Resultsmentioning
confidence: 99%
“…The negative values of the binding energies suggest that all the considered vdWHs are energetically stable within the same order of magnitude as other vdW heterostructures. For instance, graphite (−116 meV), 70 blue P/BSe (−133 meV), 71 MoS 2 /SnS 2 (−100 meV), 19 BP/blue P (−120 meV), 72 SnS 2 /PbI 2 (−124 meV), 73 Cd/C 2 N (−80 meV) 74 and SiAs 2 /GeP 2 (−77.4 meV). 47 From binding energy analyses of the two different staking modes, we have concluded that the heterostructure materials prefer the AA-stacking mode over AB.…”
Section: Resultsmentioning
confidence: 99%
“…The band gap was demonstrated to change linearly with the applied electric field, and the MoS 2 /PbI 2 vdW structure transits along the track of type-II→type-I→type-II under different external electric fields, providing new perspective in the application of nanodevices. Besides the above noted 2D heterostructures, other types of vdW heterostructures, such as graphene/ MoS 2 , [161] MoSe 2 /WSe 2 , [162] SnS 2 /PbI 2 , [163] 2D alkaline-earth metal hydroxide/graphene, [164] GaSe/MoSe 2 , [137] graphene/ GeTe, [134] BP/MoSSe, [138] GaTe/CdS, [140] InSb/InSe, [165] MoS 2 / WS 2 , [166] graphene/MoTe 2 , [167] etc., have also been studied in detail regarding the modulation of the structure and property under external electric field. During these studies, the influence of various parameters such as electric field strength, interlayer distance, layer number, were systematically discussed.…”
Section: External Electric Fieldmentioning
confidence: 99%
“…90 Moreover, an external electric eld has also been reported to inuence the band structure of some special semiconductors, such as phosphorene/graphene-like GaN, a SnS 2 /PbI 2 heterostructure, and two-dimensional transition metal dichalcogenides. [91][92][93] 2D materials whose band gap is tunable play an important role in electrical and optoelectronic devices. 93 In order to investigate the potential of the SnSiGeN 4 monolayer for application in the mentioned areas, its band structure under the effect of strains ranging from −10% to 10%, and an electric eld whose magnitude is −5 V nm −1 to 5 V nm −1 is explored.…”
Section: Electronic Properties Of the Snsigen 4 Monolayermentioning
confidence: 99%